DESAIN SISTEM PEMBANGKIT LISTRIK TENAGA SURYA 1 KW MENGGUNAKAN MESIN STIRLING TIPE ALFA - Indra Fitriyanto; Gunawan Nugroho (Jurnal Teknologi Terapan, 2022)
Stirling engine can be operated by focusing sunlight using a concentrator. The Stirling engine was chosen because of its simplicity and efficiency. Stirling engine can be applied to power plants on a large or small scale. In this study, we will discuss the concentrator system for the Stirling engine on a household scale. To be able to meet the household electricity needs of 900 VA, the concentrator must produce an output power of 2254.96 W with a concentrator area of 15.38 m2. First of all, aperture sizing is done to get the best aperture diameter, and obtained 0.04 m. The system analysis that has been carried out shows that the efficiency of the receiver is 57.50%, the efficiency of the Stirling engine is 33.26%, and the efficiency of the generator is 95%. Thus, the Stirling engine with the concentrator as a whole system has an efficiency of 17.07%. To meet the 900 VA class household electricity needs, the system requires 5 unit of 12 V 120 Ah batteries arranged in parallel with a 1000W inverter. This study also looks at the potential of Stirling engine systems with concentrators in other areas. Based on the analysis that has been done, Surabaya is the most potential area for the manufacture of a 1 kW Stirling engine concentrator system. As for areas outside Java, Pekanbaru City is the most potential area.